Hollow fiber membrane based on reaction surface segregation and preparation method and application thereof
Through the hollow fiber membrane preparation method based on reaction surface segregation, the problem of decreased permeability caused by membrane pollution is solved, and the high permeability flux and anti-pollution performance is improved. It is suitable for treating emulsified and dissolved oils with smaller particle sizes. .
Patent Information
- Application Number
- CN202411662955.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2024-12-31
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
In the prior art, membrane contamination leads to a decrease in permeability flux, making it difficult to effectively treat emulsified and dissolved oils with smaller particle sizes.
Using the hollow fiber membrane preparation method based on reaction surface segregation, the cast film liquid is formed by heating and stirring the main polymer, segregation agent and organic solvent, and spinning and curing it in an aqueous solution of polyphenol hydroxyl polymer and metal ion precursor to form Hollow fiber membrane with high permeability flux and anti-pollution properties.
The anti-pollution performance and permeability flux of hollow fiber membranes are improved, and the complexity of surface coating and grafting operations in traditional methods is avoided, and efficient oil droplet retention and flux recovery rate is achieved.
Smart Images

Figure CN119215678A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to a method for preparing a hollow fiber membrane based on reaction surface segregation, and relates to the technical field of membrane separation. Background Art
[0002] Oily wastewater is widely present in industrial production processes such as oil extraction and refining, with huge discharge volumes, causing water pollution and water resource loss. According to the form in water, the oil in oily wastewater can be divided into suspended oil, dispersed oil, emulsified oil and dissolved oil. The particle size of oil droplets in emulsified oil is generally less than 10μm, and most of them are concentrated in 0.1-2μm. For emulsified oil and dissolved oil with smaller particle sizes, traditional oily wastewater treatment technologies such as flotation, filtration, centrifugation, flocculation, and biochemistry are difficult to meet the treatment needs. Membrane separation technology is a new green and efficient separation technology. Among them, ultrafiltration membrane technology can accurately screen oil droplets through membrane pores, with an oil removal efficiency of more than 90%. It has become one of the most effective technologies for deep treatment of oily wastewater.
[0003] Surface segregation technology is an in-situ anti-fouling membrane preparation method with the following advantages: (1) Surface segregation is carried out in-situ during the phase transformation process, and film formation and modification are synchronized. It can overcome the problems of easy pore blockage and difficulty in modifying membrane pores in the "modification after film formation" process, and can create a more effective polymer brush on the membrane surface; (2) Surface segregation can occur at any position of the interface formed during the phase transformation process, achieving simultaneous modification of the membrane surface and membrane pores; (3) Surface segregation is a thermodynamic and kinetic process that is synergistically regulated. By changing the thermodynamic and kinetic parameters, the modification effect can be flexibly regulated; (4) The modified surface obtained by surface segregation is a self-healing surface. If the surface modified molecules are lost, the modified molecules near the surface will automatically migrate to the membrane surface, so that the modification effect can be maintained. Summary of the invention
[0004] In view of the above-mentioned prior art, the present invention provides a method for preparing a hollow fiber membrane based on reactive surface segregation to solve the technical problem of membrane contamination leading to decreased permeate flux in the prior art. In order to solve the above-mentioned technical problem, the present invention proposes a method for preparing a hollow fiber membrane based on reactive surface segregation, comprising the following steps:
[0005] Step 1) adding the main polymer, segregation agent and organic solvent into a reaction kettle, heating and stirring, and then standing to obtain a casting solution;
[0006] Step 2) spinning the casting solution and introducing it into a coagulation bath for solidification to obtain a hollow fiber membrane; the coagulation bath is composed of an aqueous solution of a polyphenol hydroxy polymer and a metal ion precursor, wherein the mass percentage of the polyphenol hydroxy polymer is 0.1-0.5%, and the molar ratio of the metal ion precursor to the polyphenol hydroxy polymer is 1:1;
[0007] Step 3) soaking the hollow fiber membrane formed in step 2) in water to remove the influence of organic solvent and preserve it for a long time.
[0008] Furthermore, the preparation method of the present invention, wherein:
[0009] In step 1), the mass percentages of the main polymer, segregation agent and organic solvent are 10-20%: 5-10%: 70-85%; the main polymer is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyether sulfone, polysulfone, polyvinyl chloride, and polypropylene; the segregation agent is a block copolymer Pluronic F127; the organic solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone. In step 1), the temperature of heating and stirring is 60-70°C, the stirring time is 6-12h, and the standing and degassing time is 12-24h.
[0010] In step 2), in the coagulation bath, the polyphenol hydroxy polymer is one of polyacrylic acid, tannic acid, polysodium alginate or polymaleic acid, preferably polyacrylic acid, and the metal ion precursor is anhydrous ferric chloride; the temperature of the coagulation bath is 25-30°C; in step 2), the casting liquid is spun in a hollow fiber spinning machine by a non-solvent induced phase separation method, wherein the spinning speed is 8-80 m / min, the spinning pump flow rate is 5-50 mL / min, and the core liquid flow rate is 5-30 mL / min. The core liquid is water, and the temperature of the core liquid is 25-30°C.
[0011] In step 3), the shaped hollow fiber membrane is immersed in water for at least 24 hours, and the water is replaced several times during the immersion period.
[0012] The hollow fiber membrane based on reaction surface segregation prepared by the present invention is used as a microfiltration membrane or an ultrafiltration membrane in the field of water treatment.
[0013] Compared with the prior art, the present invention has the following beneficial effects:
[0014] (1) This method can not only improve the anti-fouling performance of the hollow fiber membrane, but also has a simple process and great industrial application prospects;
[0015] (2) The method for preparing the hollow fiber membrane provided in the present application is an in-situ anti-pollution membrane preparation method, which can realize in-situ modification and all-round modification of the membrane surface and pores, avoiding the drawbacks of complex surface coating and surface grafting operations and clogging of membrane pores. The prepared hollow fiber membrane has high permeation flux and excellent anti-pollution performance;
[0016] (3) Introducing trivalent iron ions into the coagulation bath promotes the rapid reaction of the polyphenol hydroxy polymer with Pluronic F127 to form a hydrogel layer. The present invention constructs a hydrophilic membrane surface by introducing polyphenol hydroxy polymer and iron ions, and resists membrane pollution through the hydration layer effect. The prepared hollow fiber membrane has high permeability and high anti-pollution performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] Figure 1 This is a scanning electron microscope image of a cross section of a hollow fiber membrane prepared in Example 1;
[0018] Figure 2 This is a comparison chart of pure water flux of hollow fiber membranes prepared in Examples 1 to 5 and Comparative Examples 1-2;
[0019] Figure 3 It is a comparison chart of the permeation flux of the hollow fiber membranes prepared in Examples 1 to 5 and Comparative Examples 1-2;
[0020] Figure 4 It is a comparison chart of the flux recovery rates of the hollow fiber membranes prepared in Examples 1 to 5 and Comparative Examples 1-2. DETAILED DESCRIPTION
[0021] The design idea of the present invention for preparing a hollow fiber membrane based on reactive surface segregation is: the preparation method adopts a one-step method to complete the preparation and simultaneous modification of the hollow fiber membrane, and through the introduction of the block copolymer Pluronic F127, a hydrogel is formed on the outer surface of the hollow fiber membrane, a hydrophilic membrane surface is constructed, and the membrane pollution is resisted by the hydration layer effect. The preparation steps are mainly: using polyvinylidene fluoride powder as the main polymer, using the block copolymer Pluronic F127 as the segregation agent, mixing the polyvinylidene fluoride powder, the block copolymer Pluronic F127 and the organic solvent, heating and stirring, and standing to degas to form a casting liquid; then, the casting liquid is spun and introduced into a coagulation bath composed of a polyphenol hydroxyl polymer and an aqueous solution of a trivalent iron salt, and the non-solvent induced phase separation method is used to spin and solidify to obtain a formed hollow fiber membrane; finally, the formed hollow fiber membrane is immersed in an aqueous solution to remove the influence of the organic solvent and preserve it for a long time.
[0022] In the preparation method of the present invention, the casting liquid is spun in a hollow fiber spinning machine, the coagulation bath, the casting liquid and the core liquid are kept at a constant temperature, and the casting liquid is squeezed out of the spinneret using a gear spinning pump under nitrogen pressurization conditions, so that it enters the coagulation bath for solidification and molding, thereby obtaining a hollow fiber membrane. The coagulation bath is a mixed solution of a polyphenol hydroxy polymer and a trivalent iron salt, and the core liquid is water; the temperature of the coagulation bath and the core liquid is 25-30°C; the specific parameters of the spinning process are: the temperature of the casting liquid and the spinning pump is constant at 25-35°C, preferably 25°C; the inner and outer diameters of the spinneret are 0.7mm and 1.4mm respectively; the distance of the air section (i.e., the distance between the spinneret and the coagulation bath liquid surface) is 5cm; the spinning speed is 8-80m / min, preferably 10m / min; the spinning pump flow rate is 5-50mL / min, preferably 10mL / min; the core liquid flow rate is 5-30mL / min, preferably 20mL / min, and the nitrogen pressure is 0.05MPa-0.2MPa, preferably 0.15MPa.
[0023] The technical solution of the present invention is further described in detail below in conjunction with the accompanying drawings, comparative examples and specific embodiments. The described specific embodiments are only used to explain the present invention and are not intended to limit the present invention.
[0024] Example 1
[0025] A hollow fiber membrane based on reactive surface segregation (referred to as "hollow fiber membrane") is prepared, and the preparation steps are as follows:
[0026] Step 1) 90 g of polyvinylidene fluoride (FR904, industrial pure), 48 g of Pluronic F127 and 462 g of N-methylpyrrolidone (i.e., the mass percentage between polyvinylidene fluoride, F127 and N-methylpyrrolidone is 15%:8%:77%) are added to the reactor of the hollow fiber spinning machine, mechanically stirred at 60° C. for 6 h, and then allowed to stand at 60° C. for 12 h for degassing to obtain a casting solution.
[0027] Step 2) The casting solution prepared in step 1) is used as a raw material, and a hollow fiber spinning machine is used for spinning. The casting solution is extruded and introduced into a polyacrylic acid-ferric chloride aqueous solution coagulation bath at room temperature (25°C) under 0.15MPa nitrogen pressure to solidify and shape the hollow fiber membrane, wherein the molecular weight of the polyacrylic acid is 5000, the mass fraction of the polyacrylic acid in the polyacrylic acid-ferric chloride aqueous solution is 0.1wt%, and the molar ratio of polyacrylic acid to ferric chloride is 1: 1. The process conditions for spinning in the hollow fiber spinning machine are: the inner and outer diameters of the spinneret are 0.7mm and 1.4mm respectively, the distance between the spinneret and the coagulation bath liquid surface is 5cm, the spinning speed is 10m / min, the spinning pump flow rate is 10mL / min, and the core liquid flow rate is 20mL / min.
[0028] Step 3) The above-mentioned spun hollow fiber membrane is immersed in deionized water for 24 hours, during which the deionized water is replaced three times to obtain a hollow fiber membrane based on reaction surface segregation.
[0029] The hollow fiber membrane prepared in Example 1 has an internal hollow structure, and the cross section shows a finger-like pore structure. The hollow fiber membrane prepared in Example 1 is encapsulated into a membrane assembly with epoxy resin AB glue. The pure water flux data of the membrane can be found in Figure 2 , its value is 284.02L / (m 2 h bar); in oil-water emulsion (pump oil 0.1wt%, sodium dodecyl sulfate 0.01wt%, water 99.89wt%), run for 30min. For the membrane permeation flux data, refer to Figure 3 , its value is 259.15L / (m 2 ·h·bar), the retention rate was 99.0%. After washing with deionized water for 30 minutes, the flux recovery rate reached 86.4%. Figure 4 shown.
[0030] Example 2
[0031] A hollow fiber membrane based on reaction surface segregation was prepared, and its preparation structure was basically the same as that in Example 1, except that in step 2, the mass fraction of polyacrylic acid in the polyacrylic acid-ferric chloride aqueous solution was changed from 0.1wt% to 0.2wt%; finally, a hollow fiber membrane based on reaction surface segregation was obtained.
[0032] The hollow fiber membrane prepared in Example 2 has an internal hollow structure, and the cross section shows a finger-like pore structure, such as Figure 1 As shown. The thickness of the prepared hollow fiber membrane is about 300 μm. Figure 2 The hollow fiber membrane prepared in Example 2 was encapsulated into a membrane assembly using epoxy resin AB glue. The pure water flux data of the membrane can be found in Figure 2 , its value is 339.75L / (m 2 h bar); in oil-water emulsion (pump oil 0.1wt%, sodium dodecyl sulfate 0.01wt%, water 99.89wt%), run for 30min. For the membrane permeation flux data, refer to Figure 3 , its value is 300.19L / (m 2 ·h·bar), the retention rate was 99.0%. After washing with deionized water for 30 minutes, the flux recovery rate reached 93.5%. Figure 4 shown.
[0033] Example 3
[0034] A hollow fiber membrane based on reaction surface segregation was prepared, and its preparation structure was basically the same as that in Example 1, except that in step 2, the mass fraction of polyacrylic acid in the polyacrylic acid-ferric chloride aqueous solution was changed from 0.1wt% to 0.3wt%, and during the spinning process using a hollow fiber spinning machine, the pressure of nitrogen pressurization was changed from 0.15MPa to 0.12MPa; finally, a hollow fiber membrane based on reaction surface segregation was obtained.
[0035] The hollow fiber membrane prepared in Example 3 has an internal hollow structure, and the cross section shows a finger-like pore structure. The hollow fiber membrane prepared in Example 3 is encapsulated into a membrane assembly with epoxy resin AB glue. The pure water flux data of the membrane is shown in Figure 2 , its value is 224.68L / (m 2 h bar); in oil-water emulsion (pump oil 0.1wt%, sodium dodecyl sulfate 0.01wt%, water 99.89wt%), run for 30min. For the membrane permeation flux data, refer to Figure 3 , its value is 201.45L / (m 2 ·h·bar), the retention rate was 99.1%. After washing with deionized water for 30 minutes, the flux recovery rate reached 83.1%. Figure 4 shown.
[0036] Example 4
[0037] A hollow fiber membrane based on reaction surface segregation was prepared, and its preparation structure was basically the same as that in Example 1, except that in step 2, the mass fraction of polyacrylic acid in the polyacrylic acid-ferric chloride aqueous solution was changed from 0.1wt% to 0.4wt%; finally, a hollow fiber membrane based on reaction surface segregation was obtained.
[0038] The hollow fiber membrane prepared in Example 4 has an internal hollow structure, and the cross section shows a finger-like pore structure. The hollow fiber membrane prepared in Example 4 is encapsulated into a membrane assembly with epoxy resin AB glue. The pure water flux data of the membrane is shown in Figure 2 , its value is 303.00L / (m 2 h bar); in oil-water emulsion (pump oil 0.1wt%, sodium dodecyl sulfate 0.01wt%, water 99.89wt%), run for 30min. For the membrane permeation flux data, refer to Figure 3 , its value is 258.46L / (m 2 ·h·bar), the retention rate was 99.0%. After washing with deionized water for 30 minutes, the flux recovery rate reached 89.1%. Figure 4 shown.
[0039] Example 5
[0040] A hollow fiber membrane based on reaction surface segregation was prepared, and its preparation structure was basically the same as that in Example 1, except that in step 2, the mass fraction of polyacrylic acid in the polyacrylic acid-ferric chloride aqueous solution was changed from 0.1wt% to 0.5wt%; finally, a hollow fiber membrane based on reaction surface segregation was obtained.
[0041] The hollow fiber membrane prepared in Example 5 has an internal hollow structure, and the cross section shows a finger-like pore structure. The hollow fiber membrane prepared in Example 5 is encapsulated into a membrane assembly with epoxy resin AB glue. The pure water flux data of the membrane is shown in Figure 2 , its value is 312.42L / (m 2 h bar); in oil-water emulsion (pump oil 0.1wt%, sodium dodecyl sulfate 0.01wt%, water 99.89wt%), run for 30min. For the membrane permeation flux data, refer to Figure 3 , its value is 287.64L / (m 2 ·h·bar), the retention rate was 99.3%. After washing with deionized water for 30 minutes, the flux recovery rate reached 90.4%. Figure 4 shown.
[0042] Comparative Example 1
[0043] A hollow fiber membrane is prepared, and its preparation steps are basically the same as those in Example 1, except that:
[0044] In step 2), the casting liquid obtained in step 1) is used as a raw material, and a hollow fiber spinning machine is used for spinning. The casting liquid is extruded under 0.15 MPa nitrogen pressure and introduced into a polyacrylic acid-ferric chloride aqueous solution coagulation bath at room temperature (25°C) to solidify and form a shaped hollow fiber membrane. The method is changed to: the casting liquid obtained in step 1) is used as a raw material, and a hollow fiber spinning machine is used for spinning. The casting liquid is extruded under 0.12 MPa nitrogen pressure and introduced into a room temperature (25°C) water coagulation bath; finally, a hollow fiber membrane is obtained.
[0045] The hollow fiber membrane prepared in Comparative Example 1 has an internal hollow structure, and the cross section shows a finger-like pore structure. The hollow fiber membrane prepared in Comparative Example 1 is encapsulated into a membrane assembly with epoxy resin AB glue. The pure water flux data of the membrane is shown in Figure 2 , its value is 313.27L / (m 2 h bar); in oil-water emulsion (pump oil 0.1wt%, sodium dodecyl sulfate 0.01wt%, water 99.89wt%), run for 30min. For the membrane permeation flux data, refer to Figure 3 , its value is 279.35L / (m 2 ·h·bar), the interception rate was 99.1%. After washing with deionized water for 30 minutes, the flux recovery rate was 81.7%. Figure 4 shown.
[0046] Comparative Example 2
[0047] A hollow fiber membrane is prepared, and its preparation steps are basically the same as those in Example 1, except that:
[0048] In step 2), the casting liquid obtained in step 1) is used as a raw material, and a hollow fiber spinning machine is used for spinning. The casting liquid is extruded under 0.15 MPa nitrogen pressure and introduced into a polyacrylic acid-ferric chloride aqueous solution coagulation bath at room temperature (25°C) to solidify and form a shaped hollow fiber membrane. The casting liquid is changed to: the casting liquid obtained in step 1) is used as a raw material, and a hollow fiber spinning machine is used for spinning. The casting liquid is extruded under 0.15 MPa nitrogen pressure and introduced into a polyacrylic acid aqueous solution coagulation bath at room temperature (25°C), wherein the molecular weight of the polyacrylic acid is 5000, and the mass fraction of the polyacrylic acid in the polyacrylic acid aqueous solution is 0.2wt%; finally, a hollow fiber membrane is obtained.
[0049] The hollow fiber membrane prepared in Example 2 has an internal hollow structure, and the cross section shows a finger-like pore structure. The hollow fiber membrane prepared in Example 2 is encapsulated into a membrane assembly with epoxy resin AB glue. The pure water flux data of the membrane is shown in Figure 2 , its value is 367.48L / (m 2 h bar); in oil-water emulsion (pump oil 0.1wt%, sodium dodecyl sulfate 0.01wt%, water 99.89wt%), run for 30min. For the membrane permeation flux data, refer to Figure 3 , its value is 325.47L / (m 2 ·h·bar), the retention rate was 99.0%. After washing with deionized water for 30 minutes, the flux recovery rate reached 87.9%. Figure 4 shown.
[0050] In summary, this method is an in-situ anti-fouling membrane preparation method. The preparation and modification of the membrane are carried out simultaneously, which can simultaneously improve the flux and anti-fouling performance of the hollow fiber membrane. The process is simple and has great prospects for industrial application. Figure 2 , Figure 3 and Figure 4 As shown, through the comparison chart of pure water flux, permeation flux and flux recovery rate of the above-mentioned Examples 1 to 5 and Comparative Examples 1 and 2, it can be found that compared with the comparative examples, the pure water flux and permeation flux of the polymer hollow fiber membrane based on surface segregation obtained by the preparation method of the present invention are improved, the retention rate remains basically unchanged, and the flux recovery rate is significantly improved, among which the comprehensive performance of the hollow fiber membrane prepared in Example 2 reaches the best value.
[0051] Although the present invention has been described above in conjunction with the accompanying drawings, the present invention is not limited to the above-mentioned specific embodiments, which are merely illustrative rather than restrictive. Under the guidance of the present invention, ordinary technicians in this field can make many improvements and changes without departing from the purpose of the present invention, which are all within the protection of the present invention.
Claims
1. A method for preparing a hollow fiber membrane based on reactive surface segregation, characterized in that: The following steps are involved: Step 1) adding the main polymer, segregation agent and organic solvent into a reaction kettle, heating and stirring evenly, and then standing to degas, to obtain a casting solution; Step 2) spinning the casting solution and introducing it into a coagulation bath for solidification to obtain a hollow fiber membrane; The coagulation bath is composed of an aqueous solution of a polyphenol hydroxy polymer and a metal ion precursor, wherein the mass percentage of the polyphenol hydroxy polymer is 0.1-0.5%, and the molar ratio of the metal ion precursor to the polyphenol hydroxy polymer is 1:1; Step 3) soaking the hollow fiber membrane formed in step 2) in water.
2. The preparation method according to claim 1, characterized in that: In the step 1), the mass percentages of the main polymer, the segregation agent and the organic solvent are 10-20%: 5-10%: 70-85%; The main polymer is selected from one or more of polyvinylidene fluoride, polytetrafluoroethylene, polyacrylonitrile, polyether sulfone, polysulfone, polyvinyl chloride, and polypropylene; The segregation agent is a block copolymer Pluronic F127; The organic solvent is selected from one or more of N,N-dimethylformamide, N,N-dimethylacetamide, dimethyl sulfoxide, and N-methylpyrrolidone.
3. The preparation method according to claim 1, characterized in that: In the step 1), the heating and stirring temperature is 60-70° C., the stirring rate is 200-600 r / min, and the stirring time is 6-12 h; and the mixture is allowed to stand at 60-70° C. for 12-24 h for degassing.
4. The preparation method according to claim 1, characterized in that: In the step 2), the polyphenol hydroxy polymer is one of polyacrylic acid, tannic acid, polysodium alginate or polymaleic acid, and the metal ion precursor is anhydrous ferric chloride.
5. The preparation method according to claim 1, characterized in that: In the step 2), the temperature of the coagulation bath is 25-30°C.
6. The preparation method according to claim 1, characterized in that: In the step 2), the casting solution is spun in a hollow fiber spinning machine, wherein the spinning speed is 8 to 80 m / min, the spinning pump flow rate is 5 to 50 mL / min, and the core liquid flow rate is 5 to 30 mL / min.
7. The preparation method according to claim 6, characterized in that: The core liquid is water, and the constant temperature of the core liquid is 25-30°C.
8. The preparation method according to claim 1, characterized in that: In the step 3), the shaped hollow fiber membrane is immersed in water for at least 24 hours, and the water is replaced several times during the immersion period.
9. A hollow fiber membrane based on reactive surface segregation, characterized in that: The hollow fiber membrane is prepared by the preparation method described in any one of claims 1-7.
10. Use of the hollow fiber membrane based on reactive surface segregation according to claim 9 as a microfiltration membrane or an ultrafiltration membrane in the field of water treatment.
Citation Information
Patent Citations
Preparation method of anti-pollution polymer-inorganic hybrid membrane
CN107349799A
Method for preparing ultra-filtration membranes with high selectivity and high permeability
CN108654385A
Multi-interpenetrating three-dimensional flexible network hydrogel composite separation membrane and preparation method thereof
CN117959961A
Preparation method and application of polymer hollow fiber membrane based on surface segregation
CN118022559A
Preparation method of non-shrinkable polyacrylic acid film
CN118254408A
Cited By
Method for preparing ultrafiltration membrane by taking polyphenol monomer as segregation agent and application of ultrafiltration membrane
CN119971798A
Hollow fiber membrane as well as preparation method and application thereof
CN120132620A
